Prognosis of J apanese patients with previously untreated metastatic renal cell carcinoma in the era of molecular‐targeted therapy - Shinohara, Nobuo; Obara, Wataru; Tatsugami, Katsunori; Naito, Sei; Kamba, Tomomi; Takahashi, Masayuki; Murai, Sachiyo; Abe, Takashige; Oba, Koji; Naito, Seiji (Cancer science, 2015)
A multicenter cooperative study was conducted to clarify the prognosis of Japanese patients with metastatic renal cell carcinoma in the era of molecular‐targeted therapy and the clinical usefulness of the Japanese metastatic renal cancer ( JMRC ) prognostic classification. Of 389 consecutive patients for whom treatment was started between 2008 and 2010 at 23 hospitals in Japan, 357 patients who received vascular endothelial growth factor receptor‐tyrosine kinase inhibitor ( VEGFR ‐ TKI ) or cytokine as initial systemic therapy were the subject of the present study. Patients were classified into three prognostic groups according to the JMRC prognostic classification. The endpoints were progression‐free survival ( PFS ) and overall survival ( OS ) after the start of the initial treatment. The median PFS and OS for the entire cohort of 357 patients were 9.1 and 27.2 months, respectively. VEGFR ‐ TKI were selected for patients with multiple organ metastases, those with liver metastasis, and those with bone metastasis. The median PFS and OS were 11.0 and 23.2 months and 5.4 and 38.2 months in the VEGFR ‐ TKI group and the cytokines group, respectively. The JMRC prognostic classification was useful as a prognostic model for PFS and OS (c‐indexes: 0.613 and 0.630 in patients who initially received VEGFR ‐ TKI and 0.647 and 0.642 in patients who received cytokines, respectively). The present study showed for the first time the prognosis of Japanese patients with metastatic renal cell carcinoma in the era of molecular‐targeted therapy. The JMRC prognostic classification may be clinically useful as a prognostic model.